El lugar del sindicalismo en los años formativos del peronismo (1946-1955). Una aproximación desde los discursos de J. D. Perón (Colección, 2018)
In the present article an approximation is made to the changes of meaning in the definition of trade unionism and its place in the organization of the Peronist movement, analyzed from the discourses of Juan D. Perón between 1946 and 1955. The objective was to trace the variations of the place assigned to trade unionism in Perón's discourse and to consider them in relation to the political dynamics of trade unionism in the Peronist movement. With this inquiry we hope to contribute to the understanding of the transitions in the organization of Peronism as a movement. As a hypothesis, it is argued that the dynamism of the senses that define unionism in Peronist discourse and its plasticity to accommodate different positions in the structure of movement is a central element to understand its durability.